Effects of the September 2005 Solar Flares and Solar Proton Events on the Middle Atmosphere in WACCM. Issue 7 (11th July 2018) - Pettit, J.; Randall, C. E.; Marsh, D. R.; Bardeen, C. G.; Qian, L.; Jackman, C. H.; Woods, T. N.; Coster, A.; Harvey, V. L.
Abstract: This work investigates middle atmosphere effects of the September 2005 solar flares and solar proton events (SPEs). X‐17 and X‐6.2 flares occurred on 7 and 9 September, respectively, while two moderate SPEs occurred on 10 and 15 September. Flare ionization and dissociation were calculated in the Whole Atmosphere Community Climate Model (WACCM) using the Flare Irradiance Spectral Model. Proton measurements from the Geostationary Operational Environmental Satellite system were used to compute solar proton ionization. SPEs are shown to have a larger impact than solar flares on the polar stratosphere and mesosphere; however, flares have a larger influence on the sunlit and equatorial lower thermosphere. The two flares differed significantly with respect to photon spectrum. The larger, X‐17 flare was stronger during the impulsive phase, while the X‐6.2 flare was stronger during the gradual phase. This resulted in the X‐17 flare causing more initial ionization but for a shorter duration. The simulated flare impacts also differed because specific wavelengths of the flares influenced the atmosphere above the model top. Model‐measurement comparisons show that WACCM captures the overall timing and spatial distribution of the observed electron enhancements, indicating a reasonable simulation of flare and SPE‐induced ionization. Both the SPEs and flares caused odd nitrogen increases in the mesosphere. Odd hydrogen produced in the lower mesosphere by the SPEs led to short‐lived ozone decreases of nearly 100%. The flares caused small temperature increases in the lower thermosphere but had no effect on the stratosphere. Plain Language Summary: This is the first study to use a global climate model to investigate the effects of solar flares on the Earth's atmosphere from the surface up to about 140 km. The model simulations confirm that a flare's energy spectrum, which differs from flare to flare, determines how the atmosphere is affected. For the flares investigated in this work, which occurred in September of 2005, the simulations show that the solar photons ionized the atmosphere for several hours, causing large increases in electron density. The ionization led to small increases in temperature and also initiated a cascade of chemical reactions that resulted in the production of reactive nitrogen oxides in the mesosphere and thermosphere. There were no significant effects of the flares on the stratosphere. This work is important because it adds to our growing understanding of how impulsive solar events such as solar flares affect the Earth's atmosphere and provides a foundation for understanding their cumulative impacts on the atmosphere and possibly climate. Key Points: The first time solar flare response has been investigated in a fully coupled climate model September 2005 solar flares affected temperature and composition of the mesosphere and the thermosphere but not the stratosphere Solar flare spectra determine the response in the atmosphere